Back Cover: Processable Rylene Diimide Dyes up to 4 nm in Length: Synthesis and STM Visualization (Chem. Eur. J. 36/2013). Issue 36 (27th August 2013) - Yuan, Zhongyi; Lee, Shern‐Long; Chen, Long; Li, Chen; Mali, Kunal S.; De Feyter, Steven; Müllen, Klaus
<x xml:space="preserve">Abstract</x> Longest planar rylene dyes hexarylene diimide (HDI) and octarylene diimide (ODI), with extended conjugated cores (2.8 and 3.7 nm in length) have been prepared by a facile syntheses. Both HDI and ODI exhibit broad and intense NIR absorption. Scanning tunneling microscopy (STM) study reveals that HDI forms ordered herringbone bilayer or multilayers when deposited at the liquid‐solid interface. For more details, see the Communication by K. Müllen et al. on page 11842 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>